Resolution Adopted by the General Assembly: the Situation in Hungary. A/RES/1312, Thirteenth Session, Agenda Item 69 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Endorses the unanimous report of the Special Committee on the Problem of Hungary dated 14 July 1958 and expresses its thanks to Committee for its objective and effective discharge of the tasks entrusted to it; expresses appreciation to its Special Representative Prince Wan; deplores the continuing repression in Hungary of fundamental rights of Hungarian people; deplores the continued refusal of the Government of USSR and the regime in Hungary to co-operate.